2022
DOI: 10.3389/fmed.2022.905798
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response to mRNA-1273 SARS-CoV-2 Vaccine in Peritoneal Dialysis Patients: Is Boostering After Six Months Adequate?

Abstract: In dialysis patients the humoral response to anti-SARS-CoV-2 vaccines is attenuated and rapidly declines over time. However, data on the persistence of the immune response in peritoneal dialysis (PD) patients are scarce, particularly after a third (booster) dose with mRNA-1273 vaccine. In this prospective cohort study, we report anti-SARS-CoV-2 antibody levels in PD patients before and after the third dose of mRNA-1273 vaccine. Six months after the second dose, anti-SARS-CoV-2 antibodies were detected in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In this regard, a booster (or third) dose was considered early for these vulnerable patients. Although evidence on the effectivity of the third dose on patients in PD is scarce, some studies have suggested a robust humoral response rise [ 14 , 15 ]. More importantly, a booster dose has been demonstrated to seroconvert patients that had previously lost their humoral immunity against SARS-CoV-2 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a booster (or third) dose was considered early for these vulnerable patients. Although evidence on the effectivity of the third dose on patients in PD is scarce, some studies have suggested a robust humoral response rise [ 14 , 15 ]. More importantly, a booster dose has been demonstrated to seroconvert patients that had previously lost their humoral immunity against SARS-CoV-2 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a continuation of our previous published studies [22,28]. The vaccination timeline of included patients and SARS-CoV-2 waves in Austria are illustrated in Figure 1A.…”
Section: Resultsmentioning
confidence: 61%
“…Several studies in dialysis patients have shown that SARS-CoV-2 antibody levels declined after the two-dose vaccination scheme and that a third vaccine dose as a “booster” induced a strong humoral response in both hemodialysis (HD) and peritoneal dialysis (PD) patients [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Most of these studies were investigating HD patients vaccinated with BNT162b2, whereas few studies focused on PD patients using mRNA-1273 [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis patients had a high vaccination rate, probably because awareness was made after publication of mortality data of patients with a 26% for the period pre-vaccination in the 2020 for patients in hemodialysis in Panama, higher than the 2% mortality for general population for that period [ 16 ]. Some studies have addressed that dialysis patients’ immune response to vaccination is worse than in general population [ 17 ], but some studies have demonstrated a robust immune response after a third dose [ 18 ]. This study was able to assess the importance of vaccination in dialysis patients, as lethality decreased from 30 to 5% once vaccination was available.…”
Section: Discussionmentioning
confidence: 99%